Penguasaan Kanoukei Mahasiswa Tahun Masuk 2018 Program Studi Pendidikan Bahasa Jepang Universitas Negeri Padang - Meza Runa Desmita; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2020)
Abstract This study discusses the mastery of kanoukei in 2018 students of Japanese language study programs at Padang State University. The purpose of this study was to determine the kanoukei mastery of 2018 students entering the Japanese Language Study Program at Padang State University. This type of research used in this research is quantitative research with descriptive methods. The population in this study were students entering 2018 Japanese Language Education Study Program, Padang State University, amounting to 62 people. The sample in this study amounted to 30 people. The data of this study are the kanoukei mastery test scores for 2018 students entering the Japanese Language Study Program at Padang State University. Based on the results of the research carried out it can be concluded that the mastery of student kanoukei in 2018 in general is in the qualification "more than enough" with an average of 60.43